Morpho-meristic variations of the native and Vietnam-originated climbing perch (Anabas testudineus), collected from hatchery sources in Bangladesh - Md. Arif Shahariar; Md. Mahamudul Hassan; Swagata Aditya; Tanjina Saulin; Atika Khondokar; Mohammad Shafiqul Alam (Fisheries and Aquatic Sciences)
The freshwater climbing perch, Anabas testudineus locally known as “koi” in Bangladesh was introduced from Vietnam for commercial aquaculture that lacks morphological background. Therefore, the present study sought to explore morphological variation between native and Vietnam-originated populations of climbing perch collected from eight divisions of Bangladesh. Variations between these two strains were investigated by multivariate analysis of 10 morphometric and 7 meristic characters. However, the analysis revealed significant variation (p < 0.05) between native and Vietnam-originated climbing perch concerning morphometric characteristics such as standard length (SL), head length (HL), body depth (BD), eye diameter (ED), dorsal fin length (DFL), pelvic fin length (PVFL), and anal fin length (AFL) as well as meristic characters i.e. dorsal fin spine (DFS), caudal fin ray (CFR), pectoral fin ray (PCFR), and anal fin spine (AFS). The nonparametric Kruskal Wallis (H) test also revealed significant variation both in morphometric and meristic characteristics. Principal component analysis indicated that native and Vietnam-originated climbing perch can be distinguished from one another using the two distinctive morphological parameters-total length (TL) and PVFL. Hierarchical cluster analysis showed high divergence between the native and exotic populations in Bangladesh and successfully grouped the populations based on their strains. However, the present result might be useful whether any new morphotypes arise due to crossbreeding between native and Vietnam-originated climbing perch and/or different indoor cultural techniques applied in Bangladesh. Furthermore, broodfish selection of natural population propagation need to be carefully selected and present result may help in some cases in future.